De Novo Nano‐Erythrocyte Structurally Braced by Biomimetic Au(I)‐peptide Skeleton for MDM2/MDMX Predation toward Augmented Pulmonary Adenocarcinoma Immunotherapy. Issue 20 (18th April 2021) - Zheng, Xiaoqiang; Yan, Jin; You, Weiming; Li, Fanni; Diao, Jiajie; He, Wangxiao; Yao, Yu
Abstract: In nature, cells rely on a structural framework called the "cytoskeleton" to maintain their shape and polarity. Based on this, herein a new class of cell‐mimicking nanomedicine using bionic skeletons constituted by the oligomeric Au(I)–peptide complex is developed. The peptide function of degrading pathological MDM2 and MDMX is used to synthesize an oligomeric Au(I)–PMIV precursor capable of self‐assembling into a clustered spherical bionic skeleton. Through coating by erythrocyte membrane, an erythrocyte‐mimicking nano‐cell (Nery‐PMIV) is developed with depressed macrophage uptakes, increased colloidal stability, and prolonged blood circulation. Nery‐PMIV potently restores p53 and p73 in vitro and in vivo by degrading MDM2/MDMX. More importantly, Nery‐PMIV effectively augments antitumor immunity elicited by anti‐PD1 therapy in a murine orthotopic allograft model for LUAD and a humanized patient‐derived xenograft (PDX) mouse model for LUAD, while maintaining a favorable safety profile. Taken together, this work not only presents evidence showing that MDM2/MDMX degradation is a potentially viable therapeutic paradigm to synergize anti‐PD1 immunotherapy toward LUAD carrying wild‐type p53; it also suggests that cell‐mimicking nanoparticles with applicable bionic skeletons hold tremendous promise in offering new therapies to revolutionize nanomedicine in the treatment of a myriad of human diseases. Abstract : This work developed a new class of cell‐mimicking nanomedicine using bionic skeletons constituted by the oligomeric Au(I)–peptide complex. Through coating by erythrocyte membrane, an erythrocyte‐mimicking nano‐cell (Nery‐PMIV) is developed with depressed macrophage uptakes, increased colloidal stability, and prolonged blood circulation. Nery‐PMIV potently restores p53 and p73 in vitro and in vivo by degrading MDM2/MDMX in a ubiquitin‐dependent manner.